Sarcopenia is an Independent Predictor of Severe Postoperative Complications and Long-Term Survival After Radical Gastrectomy for Gastric Cancer: Analysis from a Large-Scale Cohort. Issue 13 (March 2016) - Zhuang, Cheng-Le; Huang, Dong-Dong; Pang, Wen-Yang; Zhou, Chong-Jun; Wang, Su-Lin; Lou, Neng; Ma, Liang-Liang; Yu, Zhen; Shen, Xian
Abstract : Abstract: Currently, the association between sarcopenia and long-term prognosis after gastric cancer surgery has not been investigated. Moreover, the association between sarcopenia and postoperative complications remains controversial. This large-scale retrospective study aims to ascertain the prevalence of sarcopenia and assess its impact on postoperative complications and long-term survival in patients undergoing radical gastrectomy for gastric cancer. From December 2008 to April 2013, the clinical data of all patients who underwent elective radical gastrectomy for gastric cancer were collected prospectively. Only patients with available preoperative abdominal CT scan within 30 days of surgery were considered for analysis. Skeletal muscle mass was determined by abdominal (computed tomography) CT scan, and sarcopenia was diagnosed by the cut-off values obtained by means of optimum stratification. Univariate and multivariate analyses evaluating risk factors of postoperative complications and long-term survival were performed. A total of 937 patients were included in this study, and 389 (41.5%) patients were sarcopenic based on the diagnostic cut-off values (34.9 cm 2 /m 2 for women and 40.8 cm 2 /m 2 for men). Sarcopenia was an independent risk factor for severe postoperative complications (OR = 3.010, P  < 0.001), but not for total complications. However, sarcopenia did not show significant association with operative mortality. Moreover, sarcopenia was an independent predictor for poorer overall survival (HR = 1.653, P  < 0.001) and disease-free survival (HR = 1.620, P  < 0.001). Under the adjusted tumor-node-metastasis (TNM) stage, sarcopenia remained an independent risk factor for overall survival and disease-free survival in patients with TNM stage II and III, but not in patients with TNM stage I. Sarcopenia is an independent predictive factor of severe postoperative complications after radical gastrectomy for gastric cancer. Moreover, sarcopenia is independently associated with overall and disease-free survival in patients with TNM stage II and III, but not in patients with TNM stage I.